Topography of nitric oxide synthesis by localizing constitutive NO synthases in mammalian kidney - Bachmann, Sebastian; Bosse, Hans Martin; Mundel, Peter (American journal of physiology, 1995)
Nitric oxide (NO) is generated from L-arginine by NO synthase (NOS). We have investigated the localization of constitutive NOS isoforms in rat, mouse, guinea pig, rabbit, pig, and human kidney. NADPH diaphorase (NADPH-d) reaction was used for histochemical detection of NOS enzyme activity, neuronal NOS (NOS I) and endothelial NOS (NOS III) were identified by specific antibody, and in situ hybridization was applied for NOS I mRNA detection. Strong presence of NOS I in macula densa (MD), previously detected in rat, was found in all species including humans. Additional NOS I-positive cells of the thick ascending limb (TALH) were defined. A clear-cut distinction between Tamm-Horsfall-protein-positive cells of the TALH and NOS I-positive cells of the TALH was shown. Ultrastructurally, NOS I was located in the cytosol. Intimate spatial relation between NOS I-positive cells and renin-containing preglomerular afferent arteriole suggests an effect of MD-derived NO on the juxtaglomerular granular cells. In the renal vasculature, both NADPH-d and NOS III were located in the endothelium of cortical and medullary vessels, whereas the muscle layer was unreactive. The glomerular arterioles showed stronger labeling in the efferent than in the afferent endothelium, and efferent endothelium selectively contained both NOS I and NOS III. The unique morphology of efferent endothelial cells indicates a particular role for NO in this vessel segment. At the capillary level, only the glomerular tuft showed NOS-positive endothelia. A subpopulation of renal nerves containing NADPH-d and NOS I was found in perivascular connective tissue and near pelvic epithelium. These results demonstrate a wide distribution of two constitutive NOS isoforms in the kidney of various animal species including humans. The distinct location of both isoforms in the cortex confirms that NO plays a crucial role in local glomerular signaling events.